Identification and antimicrobial susceptibility of obligate anaerobic bacteria from clinical samples of animal origin - BARQUERO-CALVO, ELIAS (2015)
The etiology of veterinary infectious diseases has been the focus of considerable research, yet relatively little is known about the causative agents of anaerobic infections. Susceptibility studies have documented the emergence of antimicrobial resistance and indicate distinct differences in resistance patterns related to veterinary hospitals, geographic regions, and antibiotic-prescribing regimens. The aim of the present study was to identify the obligate anaerobic bacteria from veterinary clinical samples and to determinate the in vitro susceptibility to eight antimicrobials and their resistance-associated genes. 81 clinical specimens obtained from food-producing animals, pets and wild animals were examined to determine the relative prevalence of obligate anaerobic bacteria, and the species represented. Bacteroides spp, Prevotella spp and Clostridium spp represented approximately 80% of all anaerobic isolates. Resistance to metronidazole, clindamycin, tetracycline and fluoroquinolones was found in strains isolated from food-producing animals. Ciprofloxacin, enrofloxacin and cephalotin showed the highest resistance in all isolates. In 17%, 4% and 14% of tetracycline-resistant isolates, the resistance genes tetL, tetM and tetW were respectively amplified by PCR whereas in 4% of clindamycin-resistant strains the ermG gene was detected. 26% of the isolates were positive for cepA, while only 6% harbored the cfxA (resistance-conferring genes to beta-lactams). In this study, the obligate anaerobic bacteria from Costa Rica showed a high degree of resistance to most antimicrobials tested. Nevertheless, in the majority of cases this resistance was not related to the resistance acquired genes usually described in anaerobes. It is important to address and regulate the use of antimicrobials in the agricultural industry and the empirical therapy in anaerobic bacterial infections in veterinary medicine, especially since antibiotics and resistant bacteria can persist in the environment